THE FUNCTION OF SWEARING IN DONALD TRUMP’S UTTERANCES DURING PRESIDENTIAL DEBATE IN 2016 - Dedek Mahiroh; Meisuri Meisuri; Lidiman Sahat Martua Sinaga (LINGUISTICA, 2018)
The study deals with the function of swearing in Donaldtrump’sutterances during the presidentialdebate. In this study, the researcher focuses onthe typesand the functionsof swearing inDonald Trump’s utterances during the presidential debate.The research used the descriptive qualitative method.The data were taken from video’s transcript ofAmerica presidential debate in 2016. There were three video’s transcript used as the sample, they were first presidential debate broadcasted on September 26th,2016, second presidential debate broadcasted on October 9th, 2016 and third presidential debate broadcasted on October 19th, 2016.Based on the analysis of data, the findings said that there were five types of swearing in Donald Trump’s utterances during a presidential debate in 2016 namely politic term, religious matter, death term, animal term, and sex or copulative term.However, there were three functions of swearing in Donald trump’s utterances during a presidential debate in 2016 namely descriptive swearing, abusive swearing, and idiomatic swearing. Keywords:Swearing, Taboo words, Sociological Approach, US presidential debate in 2016, Donald Trump